Chapter 7 Left-handedness attempts at dyslateralization, duress, and performance in reading and writing - LAINY, Rochambeau (Taylor & Francis, 2022)
This chapter deals with the sensorimotor predominance in connection with hindrances to the learning of reading and writing in a group of 120 left-handed pupils, aged 9 to 20, educated in ten schools located in the western and southern departments of Haiti. Manual, visual and auditory preference is studied in relation to linguistic performance in left-handed students, sometimes ignored but often forced to favor the side which hemispherical development has not made naturally dominant. Poor performance was certainly observed, but it is not directly linked to these students’ left-handedness. It is preponderantly the consequence of asymmetries contrary to the cerebral hemisphere, of a somewhat underhand attempt at 'dyslateralization', due to the failure of an educational system characterized by shortcomings and prejudices built around the phenomenon of laterality and problems emanating from unsuitable educational and linguistic practices. This creates constraints that prevent these students from thriving. Because the teaching strategies, methods and the school environment are designed and adapted to benefit right-handed students, left-handed people have a disability.